Bradycardia in severely dehydrated cholera patient: A case report - Shah, Ronak (Journal of acute disease, 2025)
Rationale: Cholera is an acute diarrheal disease caused by the ingestion of food or water contaminated by Vibrio cholerae. It threatens global health and signifies a lack of proper access to clean water and sanitation. If not treated properly, cholera causes severe watery diarrhea that can lead to hypovolemic shock. Patient's Concern: A 23-year-old male patient was admitted with severe diarrhea with a frequency of fifteen to twenty loose, watery stools and was severely dehydrated. The patient developed severe bradycardia with a positive serum troponin level and no chest pain. Initial electrocardiogram on the day of admission was sinus tachycardia with a heart rate of 120 beats/min on the third day of admission, the patient developed bradycardia with a heart rate of 45 beats/min with a prolonged QT interval of 550 msec (corrected QT interval 476 msec). Diagnosis: Cholera with sinus bradycardia with prolonged QT interval. Interventions: Based on the clinical situation and the inferior vena cava status determined by ultrasound, a thorough fluid resuscitation using crystalloids was performed. The patient was then administered antibiotics: oral doxycycline 300 mg STAT and intravenous ciprofloxacin 15 mg/kg twice daily for three days. Outcomes: After 5 days of adequate hydration and antimicrobial treatment, diarrhea was resolved and heart rate improved with no electrocardiogram abnormalities. Lessons: This case report highlights the importance of timely diagnosis and managing severe diarrhea in cholera patients to prevent morbidity and mortality. Public awareness regarding cholera and its complications is necessary for the betterment of the community.